Revisiting the Corneal and Blink Reflexes for Primary and Secondary Trigeminal Facial Pain Differentiation - Zafar Ali Khan (Pain Research and Management)
Trigeminal neuralgia is often misdiagnosed at initial presentation due to close connotation with dental pain and is often over diagnosed for the very same reasons leading to numerous unnecessary surgical procedures such as peripheral neurectomy and alcohol injections, while the actual cause may remain elusive for decades. Evaluation of the neurosensory system may disclose the correct anatomical location of the etiology. The neurological examination may be clouded by the sensory deficits subsequent to previous peripheral surgical procedures. The corneal and blink reflexes are integral measures of the trigeminal and facial neurosensory assessment, and their abnormal function may facilitate the identification of intrinsic disease of the brain stem. These reflexes can be employed to discover pathological lesions including intracranial space-occupying trigeminal, lateral medullary, cerebral hemispheric lesions, and degenerative diseases of the central nervous system. Dental surgeons and oral and maxillofacial surgeons should consider corneal reflex in neurological assessment of patient presenting with trigeminal neuralgia-like symptoms. Failure to evaluate corneal sensitivity may lead to delayed or inaccurate diagnosis and unsuitable or redundant treatment interventions. This simple noninvasive reflex can be performed by chair-side and may provide significant information regarding the origin of facial pain and is an invaluable part of clinical methods especially in remote and peripheral healthcare center practitioners where sophisticated radiographic investigations such as computed tomography and magnetic resonance imaging may not be available.